Estimating Demand of India and China for Indonesian Palm Oil Export - Ambiyah Abdullah (Journal of World Trade Studies, 2011)
There has been a shift in the destination of Indonesian palm oil exports from Europeanmarkets to India and China in recent years. This article aims to estimate the demand of these two countries for Indonesian palm oil exports. This article argues that price supporting policies play an important role behind the increase in the quantity of the demand for Indonesian palm oil exports. This article concludes that it is crucial to disaggregate palm oil data into crude palm oil data and refined palm oil products. This is because it can contribute significantly to improve the results of the price estimation and income elasticity of Indonesian palm oil export for both India and China.